2020
DOI: 10.7717/peerj.9293
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence analyses of Glaesserella parasuis isolates reveals extensive genomic variation and diverse antibiotic resistance determinants

Abstract: Background Glaesserella parasuis (G. parasuis) is a respiratory pathogen of swine and the etiological agent of Glässer’s disease. The structural organization of genetic information, antibiotic resistance genes, potential pathogenicity, and evolutionary relationships among global G. parasuis strains remain unclear. The aim of this study was to better understand patterns of genetic variation, antibiotic resistance factors, and virulence mechanisms of this pathogen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
2
2
1
Order By: Relevance
“…Phylogenetic analysis revealed three primary lineages, LI, LII and LIII. This is in contrast with a recently published study from China [ 23 ] that showed G. parasuis isolates clustering into two main primary lineages comprised of STs not found in the present study, highlighting the high genetic variation found within the species.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analysis revealed three primary lineages, LI, LII and LIII. This is in contrast with a recently published study from China [ 23 ] that showed G. parasuis isolates clustering into two main primary lineages comprised of STs not found in the present study, highlighting the high genetic variation found within the species.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the genes, bcr (bicyclomycin resistance ) , ksgA (kasugamycin resistance), bacA (bacitracin resistance ) , sul2 (sulfonamide resistance, and aph (3’’)-Ib (streptomycin resistance) were detected in almost 100% of the isolates. Consistent with this study, bcr , ksgA , and bacA genes were highly prevalent in G. parasuis isolates in a recent study [ 23 ]. Some of these highly prevalent genes encode resistance to antibiotics not commonly used in swine production.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is a broad genetic variability within the G. parasuis species mediated through plasmids and/or transposons [ 22 ]. A phylogenic analysis reported the existence of two main lineages, namely, lineages I and II, revealing an association with serovars, countries, and multilocus sequence types.…”
Section: Introductionmentioning
confidence: 99%
“…A G. parasuis strain from Switzerland was identified to be part of lineage I, which mainly comprises serovars 5, 12, and 14. Lineage II predominantly includes serovars 2 and 10 [ 22 ]. Recently published studies about the distribution of G. parasuis in North America, Europe, and Asia found that the geographic prevalence of molecular serovars varied slightly among different countries; however, due to the variable sizes of the examined samples, no differences in serovar prevalence could be determined [ 23 ].…”
Section: Introductionmentioning
confidence: 99%